Good Living Goals. A proposal for the construction of a global trans-development (Alternautas, 2022)
The proposal of an alternative global agenda to SDGs is the result of a trans-modern and trans-disciplinary second order research program. We organized two international discussion groups: one in Quito, Ecuador, and the other one in Salamanca, Spain, in July 2017, with the participation of twenty-two academic experts in Buen Vivir, de-growth and trans-development - eleven men and eleven women from thirteen different counties. From the transcription of their records we extracted a draft of proposal of Good Living Goals. Then at the end of 2017 and at the beginning of 2018 we administered an online survey to validate our proposal. This survey was answered by 122 experts (61 men and 51 women) – academics, researchers, consultants, stake-holders and social activists, from 20 different countries. We wrote the final version of the proposal of Good Living Goals using the results of this survey as an input. Our reflection was not intended to slow down the institutional implementation of SDGs, but generate a collective consciousness within the academy, social movements and international collaborators, which would allow a new post-2030 agenda based on goals that were not even included in the 2030 agenda.